IMPLEMENTASI MULTIMEDIA INTERAKTIF BERBASIS ANDROID MATERI FAKTOR BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V MI TARBIYATUL ULUM - Chofifah Dwi Aprilia; Wahyu Henky Irawan; A. Nurul Kawakip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is a fundamental subject that plays a crucial role in developing logical and systematic thinking skills. However, many students struggle to understand mathematical concepts in practice, particularly in topics like number factors, including the Least Common Multiple (LCM) and Greatest Common Factor (GCF). This difficulty often arises due to reliance on conventional teaching methods, such as lectures and repetitive exercises, with limited media like textbooks and whiteboards. Such an approach reduces student motivation and hinders their comprehension of LCM and GCF. This study aims to determine whether the Android-based interactive multimedia "KPK FPB Fun" can improve mathematics learning outcomes at MI Tarbiyatul Ulum. The research employs a quantitative method with a one-group pretest-posttest design. The participants consisted of 20 fifth-grade students from MI Tarbiyatul Ulum. Data were collected using 10 multiple-choice test questions and analyzed with a paired sample t-test. The results showed a significance value of <0.001 (<0.05), leading to the acceptance of the alternative hypothesis. This indicates a significant difference in learning outcomes after applying the "KPK FPB Fun" interactive multimedia. Thus, it can be concluded that the Android-based multimedia effectively improves the mathematics learning outcomes of fifth-grade students at MI Tarbiyatul Ulum.